Cinema and criminology: gender and race. Inter-sectional narratives in “The Color Purple” (2018)
Crime is a cultural product that suggests different views on forms of control, punishment and justice. Cinema crime” plays an important role for criminological knowledge, as it constitutes a form of popular criminology. The intersections between deviation, crime, control and their different symbolic representations in cinema became an object of interest for cultural criminology. The article analyzes images and discourses on violence, from an inter - sectional perspective (gender and race) of feminist criminological semantics, in the film “The Color Purple”. In the film adaptation of Alice Walker’s literary work, the images capture moments from the original work. In the universe portrayed by Spielberg, the scenes refer to contemporary issues debated by gender theories, and especially by feminist criminology, open to intersections of race. The path taken in this article aims to highlight the potential of cinematographic language to discuss and broaden the debate on issues relevant to the different criminological paradigms.